Comparison of titanium nitride and high-entropy coatings on parts of industrial plants - Yurov, V.M.; Eremin, E.M.; Guchenko, S.A. (Journal of Physics: Conference Series, 2021)
The task of the work is to establish a relationship between the main parameters of high-entropy CuZrTiNiCr coatings and their mechanical properties on parts of industrial enterprises with classic titanium nitride coatings. The technique is based on the use of mechanical alloying methods for the synthesis of high-entropy alloys and the production of magnetron targets from them. The application of titanium nitride coatings and high-entropy CuZrTiNiCr coatings on the parts was carried out on an NNV-6.6I1 installation. Establishment that high-entropy CuZrTiNiCr coatings have a density of 5.72 g/cm3, and the density of titanium nitride coatings is 5.44. The microhardness of high-entropy coatings is 14.1 GPa, while for titanium nitride coatings it varies over a wide range 20.2 GPa. The friction coefficient of titanium nitride coatings changes 0.4-0.5, which is 10 times higher than that of the high-entropy CuZrTiNiCr coating - 0.04. This antifriction property of the high-entropy coating on the parts of industrial enterprises leads to greater wear resistance and a longer service life, in comparison with classical titanium nitride coatings. Titanium nitride coatings on industrial parts were found to be 10 times less effective than highentropy CuZrTiNiCr coatings. This is due to the wear resistance of these coatings, which is due to the very low coefficient of friction and low surface energy.
Keywords: high-entropy coatings; titanium nitride; hardness; friction; wear resistance; phase composition